2015
DOI: 10.1002/jssc.201500349
|View full text |Cite
|
Sign up to set email alerts
|

Purification of vandaterosides from Vanda teres (Orchidaceae) by stepwise gradient centrifugal partition chromatography

Abstract: Vandaterosides are polar glucosyloxybenzyl eucomate derivatives found in Vanda teres (Orchidaceae), which display biological activities that slow the skin ageing process. In order to obtain larger quantities to allow us to go further in the bioassays, the hydroalcoholic extract of aerial parts (leaves and stems) of V. teres were fractionated by centrifugal partition chromatography, combining isocratic, gradient, and dual elution modes. The first fractionation was performed on the extract maintained in the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Vandaterosides, which are glucosyloxybenzyl eucomate derivatives, were first discovered in Ple. Teres stems 49 . In a previous study, human immortalized keratinocyte cell lines (HaCaT) stimulation with eucomic acid and vandateroside II was shown to upregulate cytochrome c oxidase without enhancing mitochondrial biogenesis 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Vandaterosides, which are glucosyloxybenzyl eucomate derivatives, were first discovered in Ple. Teres stems 49 . In a previous study, human immortalized keratinocyte cell lines (HaCaT) stimulation with eucomic acid and vandateroside II was shown to upregulate cytochrome c oxidase without enhancing mitochondrial biogenesis 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Vandaterosides which are eucomate derivatives were isolated from different solvent fraction prepared from Vanda teres extract. 58 In another study conducted using three solvents namely Petroleum ether, ethanol and methanol of plant extraction, it was found that in petroleum ether extract alkaloid, saponin and tannin were present, and in ethanolic extract alkaloid, steroid, saponin and tannin were found to be present whereas in the methanolic extract alkaloid, reducing sugars, flavonoid, steroid, saponin and tannin were present. 59…”
Section: Vanda Teresmentioning
confidence: 98%